The furniture handbook : a guide to choosing, arranging, and caring for the objects in your home - Ramstedt, Frida (Clarkson Potter, 2024)
"The comprehensive guide to living with furniture, no matter your style, from the author of The Interior Design Handbook. Interior-design sensation Frida Ramstedt changed how we think about designing a harmonious home with her book The Interior Design Handbook. Now she brings that same authoritative and comprehensive focus to this complementary guide that's all about the most essential and functional items within your home. No matter your style of home, we all want our spaces to feel inviting and comfortable. And the key to that is quality furniture that supports your lifestyle. The Furniture Handbook shares the foundational rules of choosing, arranging, and caring for the furniture in every room of your home. From selecting the perfect size dining table and seating that fits your family to arranging your living room pieces for the best flow, the basic principles that interior designers use and that everyone should master are provided"--